A New Generic Single-Channel Ear-EEG Recording Platform - Hongyu Liang; Rong Liu (Proceedings, 2022)
It has been demonstrated that electroencephalography (EEG) signals can be acquired from electrodes placed on an earpiece inserted into the ear, and the interest in dry ear-EEG has increased in recent years. However, the challenge is to find an excellent durable electrode material, with which the stable quality signals can be collected after repeated insertions. To achieve a sustained ear-EEG recording platform, a new generic earpiece designed with PDMS and the AgCl powder sintered electrode is proposed in this paper. The platform’s characteristics are evaluated with an alpha band modulation and auditory steady-state response (ASSR), with the inclusion of different ear sizes of subjects. Recordings from the prototyped generic ear-EEG platform are compared to conventional scalp EEG recordings. The ear-EEG electrode exhibits good wear resistance. After repeated insertion and removal of the electrode, the quality of the signal acquired by the electrode was stable, and statistically significant (p < 0.05) responses were measured for ASSR paradigms.